A comparative study of the efficacy and safety of oral apremilast versus oral methotrexate in patients with moderate to severe chronic plaque psoriasis - Shetty, Vinma H.; Goel, Saumya; Murali Babu, Amita; Eram, Hafsa (International Journal of Research in Dermatology, 2018)
Background: Psoriasis is a chronic, inflammatory systemic disease. Methotrexate acts by inhibiting dihydrofolic reductase enzyme. Apremilast is an oral PDE4 inhibitor approved by US Food and Drug Administration for treatment of psoriasis. Methods: This is hospital based comparative study conducted from February 2018 to August 2018. Seventy patients above 18 years of age with chronic plaque psoriasis were divided into 35 patients in each group and were treated with oral Apremilast (30 mg twice daily) and oral methotrexate (15 mg per week in three divided doses with a 12-hour interval between doses and tab folic acid on methotrexate free days) and were evaluated every 4 weeks for a period of 16 weeks and followed-up at 24th week. Outcome was assessed on basis of psoriasis area-and-severity index score (PASI), psoriasis disability index (PDI) and clinical photographs. Results: % of improvement in Group-A patients (76.8%) after 16 weeks of treatment was relatively more (p<0.05) as compared to group B (71.5%). At the end of 16 weeks PASI score in methotrexate group was statistically significant (p<0.05) as compared to group B, PDI became 17.90±3.87 in group A and was statistically significant (p<0.05) as compared to group B which was 20.34±2.98. Side effects observed were comparatively less in group A patients. Conclusions: On comparing the two drugs, methotrexate was comparatively better tolerated and had better efficacy and safety. More studies are required to further prove the efficacy of Apremilast in treatment of psoriasis.